2019
DOI: 10.1016/j.thromres.2019.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of BAY 94-9027, an extended-half-life factor VIII, during surgery in patients with severe hemophilia A: Results of the PROTECT VIII clinical trial

Abstract: Ensuring hemostasis during invasive procedures is a challenge in patients with severe hemophilia A. This analysis evaluated efficacy and safety of BAY 94-9027, an extended-half-life recombinant factor VIII (FVIII), in the surgical setting. Materials and methods: Patients participating in an open-label BAY 94-9027 clinical trial who underwent major surgery were included in the analysis. Investigator/surgeon assessment of hemostasis during surgery was the primary outcome. In addition, information about FVIII use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 13 publications
4
24
0
Order By: Relevance
“…In pathfinder 3, postoperative bleeds were reported in 8.2% (n = 4/49) of procedures. In other studies, postoperative bleeds were reported with rFVIIIFc in 4.3% (n = 1/23), 12 with BAX 855 in 23.8% (n = 5/21) 11 and with BAY 94‐9027 in 7.7% (n = 2/26) 18 of major/minor surgeries, respectively. A variety of major orthopaedic/non‐orthopaedic procedures were successfully performed with turoctocog alfa pegol.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In pathfinder 3, postoperative bleeds were reported in 8.2% (n = 4/49) of procedures. In other studies, postoperative bleeds were reported with rFVIIIFc in 4.3% (n = 1/23), 12 with BAX 855 in 23.8% (n = 5/21) 11 and with BAY 94‐9027 in 7.7% (n = 2/26) 18 of major/minor surgeries, respectively. A variety of major orthopaedic/non‐orthopaedic procedures were successfully performed with turoctocog alfa pegol.…”
Section: Discussionmentioning
confidence: 81%
“…Twenty‐one major and five minor procedures were reported with BAX 855 treatment, with haemostasis successful in all procedures 11 . Similarly, haemostasis was rated effective for all 26 major surgeries undertaken in adults/adolescents using BAY 94‐9027 18 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A second distribution compartment could not be identified for damoctocog alfa pegol (CV on Q = 103%); the PK of damoctocog alfa pegol was adequately described by a onecompartment model (technically, the PK of damoctocog alfa pegol was described by a two-compartment model fixing Q to a very small value [0.001]), while a two-compartment model was used for rurioctocog alfa pegol. Compared with damoctocog alfa pegol, the CL of rurioctocog alfa pegol was significantly increased by 21% (95% CI, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. This effect was consistent across patients with an estimated betweenpatient variability of 11.5% CV and 17 out of 18 patients having a CL value in favor of damoctocog alfa pegol compared with rurioctocog alfa pegol, respectively.…”
Section: Population Pk Modeling and Time To Threshold Simulationmentioning
confidence: 83%
“…Rurioctocog alfa pegol is a full-length rFVIII product that has been PEGylated at its B-domain, with a branched 20-kDa PEG molecule (Advate®; Baxter, USA) [12,13]. Rurioctocog alfa pegol was first licensed in 2015, and damoctocog alfa pegol in 2018, for the treatment of hemophilia A, based on efficacy and safety data from their respective pivotal phase 2/3 clinical trials [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%